Biomarker-based guideline-directed medical therapy of heart failure: the gap between guidelines and clinical practice - Berezin, A. E.; Berezin, A. A.; Березін, Олександр Євгенійович (London: EMJ, 2021)
Current clinical recommendations provided by the 2016 European Society of Cardiology (ESC) and 2017 American College of Cardiology (ACC)/American Heart Association (AHA)/Heart Failure Society of America (HFSA) are substantially distinguished in the use of circulating biomarkers in the management of heart failure (HF). To date, natriuretic peptides continue being the universal biomarkers used in diagnosis, risk stratification, and prediction of cardiovascular death, all-cause mortality, and HF-related outcomes for patients with both phenotypes of HF. However, biomarkers of fibrosis and inflammation, including soluble suppressor of tumourgenicity 2 and galectin-3, were able to increase predictive ability of natriuretic peptides in HF patients regardless of cardiovascular risk-factor presentation and HF phenotypes. Therefore, there are many various biomarkers describing several pathophysiological processes such as fibrosis, inflammation, oxidative stress, neurohumoral activation, extracellular matrix turnover, and vascular reparation, that play a pivotal role in the natural evolution of HF. This review discusses whether multiple biomarker models are more effective than a single biomarker in improving risk stratification strategies in patients with HF. It emphasises how in routine clinical practice, the multiple biomarker approach to elicit response to therapy of HF and predict clinical outcomes is rare, probably because of the relatively high cost, low affordability, lack of clear recommendations for clinical implementation, and significant disagreements in the interpretation of the data obtained.